The Interaction of Three Types of Undernutrition and Health Insurance Subscriptions at the Children in the Karawang Coastal Area, Indonesia: Interaksi Tiga Jenis Kekurangan Gizi dan Langganan Asuransi Kesehatan pada Anak di Pesisir Karawang, Indonesia - Linda Riski Sefrina; Ratih Kurniasari; Milliyantri Elvandari; Annisa Ratri Utami; Asep Malinda Aiboga; Neng Ulya (Amerta Nutrition, 2022)
Background: Three types of undernutrition including stunting, underweight, and wasting, are a global public health problem. In terms of policies, guidance, programming, and financing, they are mostly separated while all of them are caused by poor diet. Objectives: This study aimed to identify the association of underweight and wasting status with stunting of the children and health insurance subscriptions in the Coastal Area. Methods: This was a cross-sectional study involving children aged 6 to 59 months. Demographic backgrounds were obtained from parents through a questionnaire. Height and weight were measured. Z-scores for height-for-age, weight-for-age, and weight-for-age were determined and classified using WHO AnthroPlus software. The binary logistic regression test was used to identify the association of variables. Results: A total of 108 children participated in the study. The prevalence of stunting, being underweight, and wasting was 21.3%, 21.3%, and 13.9% respectively. It was found that most demographic characteristics (age, gender) and health insurance were similar in each of the undernutrition types, except for age level in stunting children. The risk of stunting in underweight children is significant differences, but not for wasting children in the coastal area. This study also shows that there is a significant correlation between the incidence of stunting with wasting and being underweight in children in the coastal area of Karawang. Conclusions: Overall, underweight children tend to have a stunting risk. The policy and community-based program need to not focus on one category of undernutrition only, but also on other types of undernutrition simultaneously, with the aim that nutritional problems in children can be handled holistically.